S1PR2 Inhibition Attenuates Allergic Asthma Possibly by Regulating Autophagy - Liu, Hanye; Li, Liangchang; Chen, Zhengai; Song, Yilan; Liu, Weidong; Gao, Ge; Li, Li; Jiang, Jingzhi; Xu, Chang; Yan, Guanghai; Cui, Hong (Frontiers in Pharmacology, 2021)
This study is to investigate the role of Sphingosine-1-phosphate (S1P) in the asthma progression, and the involvement of autophagy. Airway remodeling mice were subjected to the HE, PAS, and Masson staining. Protein expression levels in the tissues, samples and model cells were detected with ELISA, Western blot analysis, and immunohistochemical/immunofluorescent analysis. The S1P2 receptor antagonist JTE-013 decreased the inflammatory cell infiltration and goblet cell production in asthmatic mice tissues. The IL-1, IL-4, IL-5 and serum IgE contents were decreased in bronchoalveolar lavage fluid, while the Beclin1 expression in lung tissues was decreased. The LC3B1 to LC-3B2 conversion was decreased, with increased P62 accumulation and decreased p-P62 expression. In airway remodeling mice, JTE-013 significantly decreased collagen deposition in lung tissues and decreased smooth muscle cell smooth muscle activating protein expression. In lung tissue, the expression levels of Beclin1 were decreased, with decreased LC3B1 to LC-3B2 conversion, as well as the increased P62 accumulation and decreased p-P62 expression. However, these effects were reversed by the RAC1 inhibitor EHT1864. Similar results were observed for the silencing of S1P2 receptor in the cells, as shown by the decreased Beclin1 expression, decreased LC3B1 to LC-3B2 conversion, increased P62 accumulation, and decreased p-P62 expression. The smooth muscle activators were significantly decreased in the JTE-013 and EHT1864 groups, and the EHT1864 + S1P2-SiRNA expression level was increased. S1P is involved in the progression of asthma and airway remodeling, which may be related to the activation of S1PR2 receptor and inhibition of autophagy through RAC1.